Carbon and sulfur conversion of petroleum coke in the chemical looping gasification process. (15th July 2019) - Wang, Lulu; Feng, Xuan; Shen, Laihong; Jiang, Shouxi; Gu, Haiming
Abstract: Petroleum coke is the waste from the delay coking process during petroleum refining. It is urgent to solve the problem of the effective and environmental utilization of high-sulfur petroleum coke. Chemical looping gasification (CLG) is employed in the application of petroleum coke for syngas production and sulfur recovery for the first time. The conventional steam gasification was for comparison to have a better understanding of the chemical looping process of petroleum coke. The presence of hematite improved the carbon conversion efficiency to 70.13%, although the fraction of the effective syngas decreased slightly. Experiments are conducted to evaluate the effects of temperature, steam flow rate and the sizes of fuel and hematite on the conversion of carbon and sulfur in a batch fluidized bed. The data shows that the effective syngas accounts for 83.51% and the molar fraction of H2 S/SO2 is about 2, when the fuel size was 0.1–0.3 mm, and the hematite size was 0.3–0.4 mm at the steam flow rate of 1 g/min at 900 °C. Moreover, that condition is advantageous to the further utilization of the flue gas stream for sulfur recovery via Claus process. The size of oxygen carrier has a significant influence on distribution of sulfur species releasing. The high-content sulfur in the petroleum coke did not remain on the surface of hematite and the oxygen carriers were not poisoned. As a consequence, chemical looping gasification with hematite as oxygen carrier is an excellent technique for petroleum coke conversion coupled with sulfur recovery. Highlights: The use of petroleum coke by CLG is first proposed to produce syngas and recover S. The different characteristics of steam gasification and CLG are evaluated. The contrast between petroleum coke and other fuels is explained. The syngas ratio reached more than 80% in the optimum condition for Claus process.